Do We Always Hope to Become “Better” When We Experience Envy? Effects of Incidental Envy and Social Context on Self-Improvement Behavior - Youn, Y. Jin; Park, Kiwan (ASIA MARKETING JOURNAL, 2017)
Incidental envy is known to motivate self-improvement behavior. This phenomenon occurs in part because feelings of inferiority guide subsequent behavior in a way to self-improve, after experiencing envy. However, no research has yet examined whether this tendency may be affected by social context: private versus public. Although extant literature suggests that envy generally leads to self-improvement, we demonstrate that this effect may be mitigated under public social contexts. Across two studies, we find that although incidental envy generally increases self-improvement behavior (e.g., effort exertion and charitable giving) in private social contexts, this tendency is attenuated under public social contexts. We conclude with a discussion of theoretical and practical implications of this finding.